RETAINING TALENT IN STARTUPS: FEATURES AND PRACTICAL TOOLS - Кісь, Святослав Ярославович; Кондрин , Марта Богданівна; Мазур, Юрій Мирославович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article examines the factors that influence talent retention in a startup. The author's identification of problems, challenges and opportunities of startups in the field of talent management was previously carried out, which made it possible to come to the conclusion about the need to use flexible approaches to management in this direction. To achieve the goal of the research, a focus group survey was conducted at the Ukrainian startup Lemon.io. using the author's questionnaire, which provides an assessment of the importance of talent retention factors in a startup with their preliminary division into eight categories. The obtained results of the survey made it possible, firstly, to determine the categories and factors that require priority managerial influence on talent retention from the side of the founders and managers of the startup, and secondly, to recommend the use of personally-oriented, team-wide and mixed approaches to talent retention, focusing on the assessment of the importance of factors , which influence the fact that talent remains working in the startup. It has been established that the policy of compensations and benefits, which is related to the material stimulation of talents, must be implemented with a focus on personal achievements, needs and opportunities of the employee, well-being, safety, and professional development of talents require mixed approaches, and activity in the field of leadership, corporate culture and organization of work - implementation of a uniform policy for all team members. Taking into account the importance for the entire startup team of such talent retention factors as "work environment and culture", "leadership and management", as well as "flexibility and organization of work", a detailed description of their features and practical application was carried out. At the same time, the approaches and recommendations known in the world theory and practice were used, which confirm the relevance and timeliness of the application of talent retention tools in startups.